Evaluation of soil erosion risk and sedimentation potential by using EPM model in Gabric basin- SE Hormozgan- Iran - Ahmad Ansari Lari; Maryam Ansari (مخاطرات محیط طبیعی, 2017)
Soil erosion is a complex process that is difficult to measure the true extent of that. For analysis of runoff, erosion, and sediment is needed a deep understanding of production processes.The statistical methods often are used for calculating the total volume of sediment and erosion in basins, If there are enough information and statistics relating to sediment river flow. Since the in most of the basins in the world, there are not enough statistics and information, erosion intensity will be assessed using erosion estimation technology (the same model of erosion). the purpose of this study is evaluation of erosion and sediment yield in the Gabric basin, due to dam construction on the Gabric river, using experimental model of EPM with the help of GIS and performance of these systems in the basin erosion and sediment studies and ultimately reduce sediments in the basin and behind the dam order to performed to development and control projects. In this study were obtained from geology map with 1:250000 scale, soil map available from the region, Land use/land cover map, Vegetation map, various statistics relating to the stations located around the basin and Digital Elevation Model (DEM). The results show special sediment and total sediment Gabric basin are 40.64 (m3/km2/yr) and 227725.8 (m3 /yr) respectively. Also, the amount of sedimentation and the total amount sediment generated in the basin are 243.84(ton/km2/yr) and 1666355(ton /yr) respectively, which is the classified basin of extreme class and applying various methods of erosion control are necessary for Gabric basin.